Effects of Boric Acid Gel on Vaginal Candida albicans Infections and the Local Immune System in Mice - Guo, Xiaoyu; Jing, Tingting; Li, Xiaojing; Liu, Zhao; Chen, Yongxue; Li, Yiquan; Xu, Yanyan; Gao, Hongqi (Frontiers in Immunology, 2022)
The objective was to determine the effect of 5% boric acid gel on vaginal Candida albicans (CA) infections in mice and its effect on the local immune system (i.e., Th1, Th2, and Th17). Female mice were divided into four groups, with 10 mice in each group. Mycelialsuspensions were administered into the vaginal lumen close to the cervix in groups B, F, and M. Mice in group B were given boric acid gel, and group F was treated with fluconazole gel for 30 min every 12 h. Group M was treated with sterile water, and group N was not given treatment. After the seventh day of treatment, each group was observed with the naked eye, and vaginal lavage fluid and vaginal tissue were collected. Expression levels of cytokines were measured using enzyme-linked immunosorbent assays (ELISA) and immunohistochemistry. Periodic acid Schiff (PAS) staining was used to measure the fungi in vaginal tissues. There were no significant changes in group M. In groups B and F, there was less vaginal injury and less exudate, with group B doing better than group F. The numbers of CA colonies were higher in groups B, F, and M than in group N (P < 0.01). There was less vaginal colonization of CA in group B than in group F (P < 0.01). After the seventh day of treatment, levels of IFN-γ, IL-17, IL-6, TGF-β, IL-4, and IL-10 were significantly greater in groups B, F, and M than in group N (P < 0.001); levels of IFN-γ, IL-17, IL-6, and TGF-β in groups B and F were higher than those of group M (P < 0.01), while IL-4 and IL-10 levels were significantly lower (P < 0.001). The trends of cytokine increases and decreases were more significant in group B than in group F (P < 0.05). Immunohistochemical results were similar to ELISA results. PAS staining revealed that boric acid inhibited hyphal reproduction. The boric acid significantly reduced the symptoms associated with CA vaginal infection. It inhibited the CA growth, prevented vaginal lesions, promoted the secretion of Th1 and Th17 cytokines, and reduced Th2 cytokines.